Delayed Contrast Enhancement in Magnetic Resonance Imaging and Vascular Morphology of Primary Diffuse Large B-Cell Lymphoma (DLBCL) of the Central Nervous System (CNS): A Retrospective Study - Liu, Dandan; Liu, Xiaojun; Ba, Zhaogui; Xie, Limei; Han, Jiwu; Yu, Dexin; Ma, Xiangxing (Medical science monitor, 2019)
BACKGROUND This study aimed to compare the magnetic resonance imaging (MRI) findings of primary diffuse large B-cell lymphoma (DLBCL) of the central nervous system (CNS) with delayed contrast enhancement and histological microvessel density (MVD). T1-weighted and T2-weighted contrast-enhanced and non-enhanced brain imaging were used. CNS lymphoma tissue was evaluated using primary antibodies to endothelial cells and smooth muscle cells, and histochemical staining for reticulin fibers and basement membrane, which allowed quantification of the MVD. MATERIAL AND METHODS Twenty-one patients with histologically confirmed primary DLBCL of the CNS underwent pre-contrast-enhanced and postcontrast-enhanced MRI. Histology of the CNS lymphoma tissue included immunohistochemical staining with antibodies to CD34 for vascular endothelial cells and alpha smooth muscle actin (ASMA) for vascular smooth muscle cells, and histochemical staining included periodic acid-Schiff (PAS) and silver staining for reticulin fibers to evaluate microvessel density (MVD). RESULTS In primary DLBCL of the CNS, a positive correlation was found between the degree of necrosis and the size of the lymphoma (r=0.546, P=0.01). Delayed imaging enhancement was significantly correlated with the number of mature vessels, MVD, basement membrane, and reticulin fibers (r=0.593, 0.466, 0.446 and 0.497, respectively). Standardized ß regression coefficient analysis showed that the MVD, PAS-positive structures, the number of mature vessels, and reticulin fibers, were significantly associated with delayed enhancement on MRI (ß values, 0.425, 0.409, 0.295, and 0.188, respectively). CONCLUSIONS In primary DLBCL of the CNS, delayed imaging enhancement on MRI may be due to reduced neovascularization and vascular infiltration by lymphoma cells.